Analysis of the Role of Teachers in Character Education Management Based on Local Wisdom (A Multi-Site Study at SDN Ledug 1 and SDN Pecalukan 1, Prigen District) - Maya, Siska Dwi; Thohirin, Akhmad; Wahyudi, M. Furqon (The Future of Education Journal, 2026)
This research is driven by the urgent need to address moral degradation among students by integrating local wisdom into the character education framework. The study aims to analyze the role of teachers in managing character education based on local wisdom through a multi-site study at SDN Ledug 1 and its affiliated sites. Specifically, it examines how teachers plan, implement, and evaluate character-building activities that laverage indigenous values  to foster student integrity and cultural identity. A qualitative approach with a multi – site study design is employed, utilizing data collection techniques such as in-dept interviews, participant observation, and documentation analysis. Data validity is ensured through source and method triangulation, while cross-site analysis is used to identifty patterns in teacher roles across different contexts. The findings are expected to reveal that teachers act as role models, motivators, and evaluators who successfully bridge traditional values with modern pedagogical prctices. This management process creates a synchronized educational environment where local wisdom serves as the primary foundation for student behavior. The results of this study are intended to provide a strategic model for schools to strengthen character education by optimizing the professional role of the teacher within a culturally relevant management system.